Interaction of Urban Heating and Local Winds During the Calm Intermonsoon Seasons in the Tropics. Issue 21 (7th November 2017) - Ooi, M. C. G.; Chan, A.; Subramaniam, K.; Morris, K. I.; Oozeer, M. Y.
Abstract: Rapid urbanization of cities has greatly modified the thermal and dynamic profile in the urban boundary layer. This paper attempts to study the interaction of urban heating and the local topographic‐induced flow circulation for a tropical coastal city, Greater Kuala Lumpur, in Malaysia. The role of sea‐and‐valley‐breeze‐orientated synoptic flow (SBOS) on the interaction is determined by comparing two intermonsoon periods. A state‐of‐the‐art numerical model, Advanced Research Weather Research and Forecasting model, is used to identify the influence of urbanization through modification of urban surfaces. The model reasonably reproduces the vertical sounding data and near‐surface weather parameters. The diurnal urban heating pattern is attributed to three predominant factors: (i) weak under calm and clear‐sky condition (morning heating), (ii) weak under larger atmospheric moisture content (late afternoon convection), and (iii) largest (1.4°C) due to differential cooling rate of urban and rural surface at night. The interaction of urban thermals and upper level SBOS affects the effect of urbanization on local circulation during the day. The urban thermals reduce the weak opposing SBOS (<2 m s −1 ) and enhance the inflow of moisture‐rich sea breeze passage. This increases the intensity of downwind convective precipitation during late afternoon. On contrary, the strong opposing SBOS (>2 m s −1 ) suppresses the vertical lifting of urban thermals and decelerates the sea breeze front. It is discovered that the interaction of urban heating and topographic‐induced flow is interdependent while the synoptic flow plays a critical role in modifying both factors, respectively. Key Points: The urban heating profile is greatly driven by cloud cover, atmospheric moisture content, and differential cooling rate The presence of urban significantly alters the onset and strength of topographic‐induced flow in the coastal metropolitan Sea‐and‐valley‐breeze‐orientated synoptic flow shows great influences on the interaction of urban and topographic‐induced flow